(untitled) (Reflection and Critique Law Magazine, 2023)
The discussion about economic benefits and the control of the petroleum and natural gas is centenary and surrounded by political and social conflicts, in national or international fields. In Brazil, the economic driving of these commodities has varied since the decade of 1930 and 1940 with the discussion of whom should explore it (for instance que campaign “O petróleo é nosso”) and it comes until nowadays with two applicable models of exploration: Concession (Law 9.478/1997) and Production Sharing (Law 12.351/2010). What is intended to analyze is: to verify in which model of exploration the economic sovereignty is best respected, using historical, economic, and juridical reflections, as well as empirical analyze of already occurred auctions in both models. Beyond the advantages and anachronisms from each model, it can be affirmed the inexistence of a better model in general, when considered the sovereignty as relevant operational concept. Its necessary to realize that the guarantee of the sovereignty – beginning object – in the matter of the petroleum and natural gas must be sought in a set of factors, always under the permanent surveillance of civil society in many aspects of the social control. Keywords: Economic sovereignty. Petroleum. Exploration models. Juridical economic analyze.